The Influence of Social Media Marketing and Customer Engagement on Els Coffee’s Brand Awareness as a Pioneer of Lampung’s Leading Coffee - Sona Sonia Rafika; Satria Bangsawan (PT FORMOSA CENDEKIA GLOBAL, 2023)
Marketing done digitally especially through social media makes it easier for businesses to do promotions and can reach consumers widely. Broad reach can also make a brand or business itself easier to recognize by many people. This study aims to examine the effect of Social Media Marketing and Customer Engagement variables on Brand Awareness. This research was conducted quantitatively on 108 respondents. The research was conducted on all Lampung people who know about Els Coffee on Instagram and have purchased Els Coffee products. The method used is IMB SPSS in 2022. Statistical results after hypothesis testing show that the results indicate that hypotheses one, two, and three are proven correct, and it can be concluded that Social Media Marketing has a positive and significant effect on Brand Awareness, and Customer Engagement has a positive effect on Brand Awareness.